Atmospheric oxygen over Phanerozoic time - Berner, Robert A. (The National Academy of Sciences, 1999)
It is quite possible that the level of atmospheric oxygen has varied (roughly between 15 and 30% O(2)) over the past 550 million years. This variation is suggested by modeling of the carbon and sulfur cycles, by the excessive sediment burial of organic matter that accompanied the advent of large vascular land plants, and by recent physiological studies that relate to biological evolution.